2015
DOI: 10.1055/s-0035-1548801
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fish Oil, Vitamin D and Protein on URTI Incidence in Young Active People

Abstract: Upper respiratory tract infection (URTI) is a frequent illness among athletes. We investigated the effect of a multi-nutrient supplement (vitamin D, fish oil and protein) on the occurrence of URTI in young active people. Forty-two young recreational athletes were randomly assigned to receive either a supplementation (550 mg DHA, 550 mg EPA, 10 µg vitamin D3 and 8 g whey protein) or placebo for 16 weeks. Unstimulated saliva samples were collected by passive drool. Samples were analysed for IgA (sIgA) concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…One observational study [15] showed significantly greater symptom severity scores among vitamin D deficient athletes. In contrast, two RCTs [12,14] (1 of which was conducted among vitamin D insufficient subjects) consistently showed no difference in reported symptom severity scores between supplemented and unsupplemented groups. One RCT 9 among vitamin D insufficient athletes showed that vitamin D supplemented subjects had significantly lesser total symptoms per ARI episode compared to the placebo group.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…One observational study [15] showed significantly greater symptom severity scores among vitamin D deficient athletes. In contrast, two RCTs [12,14] (1 of which was conducted among vitamin D insufficient subjects) consistently showed no difference in reported symptom severity scores between supplemented and unsupplemented groups. One RCT 9 among vitamin D insufficient athletes showed that vitamin D supplemented subjects had significantly lesser total symptoms per ARI episode compared to the placebo group.…”
Section: Resultsmentioning
confidence: 89%
“…All randomized controlled studies administered oral vitamin D3 to participants in the intervention arm given as a daily dose. One of the studies [14] did not have vitamin D as the sole supplement; it included fish oil and protein. Table 1 presents the characteristics of eligible studies (2018) [16] 53 All female --------N/A High vitamin D concentrations seen in subjects Fikratkerimov et al…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Linday et al (98) found that the simultaneous administration of cod liver oil (which contains EPA and vitamin A) and a multivitamin-mineral supplement to children led to a statistically significant (P<0.05) decrease in the mean number of URTI-related medical consultations over time. Overall, omega-3 fatty acids confer significant health benefits to patients with URTI complications and shorten the length of stay of acutely ill patients in hospital (99)(100)(101). Since omega-3 fatty acids have proven to be effective in reducing airway inflammation and bronchoconstriction, have also exhibited efficacy against viral infections (102,103), their potential for use against COVID-19 warrants further investigation (104)(105)(106).…”
Section: Amino Acidsmentioning
confidence: 99%